ANALYSIS OF THE APPLICATION OF DSN-MUI FATWA NO: 04/DSN-MUI/IV/2000 CONCERNING MURABAHAH CONTRACTS IN PEOPLE'S BUSINESS CREDIT FINANCING: STUDY ON KCP BSI LADANG RIMBA - Tri Wulandari; Sholihin, Riadhus (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
This study aims to analyze the extent of the application of the murabahah contract on People's Business Credit (KUR) products at KCP BSI Ladang Rimba, identifying the constraints of the murabahah contract which is a sale and purchase contract that is not in accordance with KUR. This research uses a descriptive method with a qualitative approach, with data collection techniques through interviews. The results showed that the application of the murabahah contract at KCP BSI Ladang Rimba has been running in accordance with the provisions of the Fatwa DSN-MUI, with a transparent and fair transaction process. During implementation, no significant obstacles were found, thanks to a strict internal control system and routine sharia audits. However, the application of the murabahah contract is not suitable because KUR is a program that is presented to help the community while the murabahah contract is a contract that allows the delegation of losses to only one party so that a more suitable contract to use is a mudharabah contract which is in the form of cooperation.